Association for Yield and Yield Related Traits in an RIL Population of Green Gram (Vigna radiata (L.) Wilezek) - , CH. Anuradha; , Mohd Abdus Subhan Salman (Archives of Current Research International, 2024)
Background: Green gram (Vigna radiata (L.) Wilczek), a significant annual legume, is a member of the family Fabaceae, subfamily Papilionoideae, and genus Vigna. Despite its importance, large-scale cultivation of green gram faces limitations due to various biotic and abiotic constraints. To address this challenge, our research is focused on the development of green gram genotypes with broader adaptability, enhanced genetic variability, and high-yielding potential. This involves a comprehensive study of the nature and magnitude of associations among yield and related traits to facilitate more effective and sustainable production practices. Methods: The present investigation was carried out at the experimental plots of Institute of Biotechnology (IBT), College farm, College of Agriculture, Hyderabad (TS). The present experiment was conducted to determine correlation and path analysis among morphological traits and their contribution towards yield among the F6 Recombinant inbred lines (RILs) in green gram. Results: Correlation estimate revealed that number of pods cluster-1, the Number of clusters plant-1, the Number of pods plant-1, Seed yield plant-1, plant height (cm), seed weight (g), and pod length (cm) showed a maximum direct contribution to seed yield both phenotypically and genotypically. Path analysis revealed that the parameters demonstrating a significant positive direct impact include days to 50% flowering, plant height (cm), number of branches plant-1 and number of clusters plant-1. The RILs for each character examined showed considerable variability. Conclusion: The green gram improvement program will benefit from a selection strategy that focuses on traits with a significant direct impact and a positive correlation with seed yield.